A study on the promotional mix of pre-service in the view of service design. Issue 8 (9th September 2019) - Qian, Chenxiang; Wu, Chih-Fu; Zhang, Zhenbo; Huang, Hsin-Yu
Abstract : Purpose: The purpose of this paper is to explore current marketing communication mixes (MCMs) in two industries, electronics home appliance stores (face-to-face interaction) and remote care (interface-mediated interaction), to propose marketing strategies from the perspective of service design and determine the relationships between service interaction patterns and MCMs in the pre-service phase. Design/methodology/approach: Six industry experts in marketing were interviewed through semi-structured interviews, the topic of which focused on the details of five MCMs and their correlations were analyzed using a customer journey maps. Finally, the MCMs were further explored to verify differences in attractiveness to customers, respectively. Findings: The result showed that the most attractive activity for the electronics home appliance stores customer is the promotion. And the four face-to-face service interaction patterns and MCMs exhibited a low correlation. In addition, the customers of remote care service argued that the personnel selling was the most attractive MCMs to them. For customers who utilize smart devices to communicate with advertisement exhibited the highest correlation coefficient. Research limitations/implications: The limitation of this study is that the research only conducts interview research on two service industries. Practical implications: This study was expected to develop improved marketing communication strategies to remedy the sales predicament induced by virtual channels and to increase people's acceptance of remote care service. Originality/value: The value of this paper is to analyze the correlation and difference of MCMs and service interaction patterns between electronics home appliance stores and remote care, and propose a structural model of MCMs for two different industries.